From This Day Forward - Snelling, Lauraine (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2016)
"Deborah MacCallister, head nurse at the Blessing hospital, has loved Toby Valders since her school days, but she's had enough of their on-again, off-again relationship. Toby truly cares for Deborah, but he's never felt like he could commit to marriage or a family. When Anton Genddarm, the new schoolteacher, comes to town, the young women of Blessing see a chance to force Toby's hand with a little strategic matchmaking"--Amazon.com.
Keywords: Nurses -- Fiction; Teachers -- Fiction; Mate selection -- Fiction; Man-woman relationships -- Fiction; Triangles (Interpersonal relations) -- Fiction; Romance fiction; Christian fiction